Baseline water quality of municipal ponds and metal removal ability of Typha latifolia L. from sewage and industrial wastewaters. Issue 12 (2nd December 2017) - Bokhari, Syeda Huma; Mahmood-ul-Hassan, Muhammad; Riaz, Yousaf; Munir, Anjum; Ali, Zeshan
ABSTRACT: Municipal effluent of three rural settings of Islamabad was assessed for physicochemical and microbiological parameters by collecting wastewater from inlet and center of ponds. Results showed that water quality was comparatively better at the center as Typha latifolia plants were growing toward the center of ponds. In another study, the wastewater treatment ability of T. latifolia was investigated by growing them in industrial and municipal effluent under greenhouse conditions. Water and plant samples were collected periodically (3rd, 10th, 17th, 24th, and 31st day after transplanting) for the measurement of Pb, Cu, and Cd concentrations. A decrease in heavy metal concentration of both effluents was observed as the experiment progressed and metal removal percentages ranged between 81% and 96%. Complementary the increase in metal concentration in plant tissues was observed over experimental period. Among plant tissues, metal concentration of Pb was highest i.e. 362 mg kg −1 in roots and 313 mg kg −1 in shoots at end of experiment. Pb, Cu, and Cd concentrations were higher in roots than shoots and hence translocation factors were less than 1.0. Metal removal efficiency was better from industrial wastewater and was in order of Pb > Cu > Cd. T. latifolia can be used for remediation of heavy metal-polluted wastewater.